Wörtliche Zitate und Anspielungen in der Alexias Anna Komnenes: Deuteros Plous - TZIATZI-PAPAGIANNI, Maria (Byzantina Symmeikta, 2023)
Verbatim Quotations and Allusions in Anna Komnene’s “Alexiad”: Deuteros Plous The paper presents and analyzes some passages from Anna Komnene’s «Alexiad», which are either verbatim quotations from or echoes of earlier texts. These were identified neither by Reinsch – Kambylis in the most recent critical edition, nor by myself in my detailed review of their edition, nor in my own relevant paper “Über Zitate und Anspielungen in der Alexias Anna Komnene’s sowie Anklänge derselben in den späteren Geschichtsschreibern”. Thus, the passages discussed in the paper contribute to the already existing research on the sources of the “Alexiad” and further clarify its intertextuality by providing new and rich material, which helps to better appreciate both the text and Anna Komnene herself within the field of Byzantine literature, historiography in particular.